2005
DOI: 10.1103/physrevd.71.054010
|View full text |Cite
|
Sign up to set email alerts
|

Near threshold enhancement of thepp¯mass spectrum inJ/Ψdecay

Abstract: We investigate the nature of the near-threshold enhancement in the pp invariant mass spectrum of the reaction J/Ψ→γpp reported recently by the BES Collaboration. Using the Jülich NN model we show that the mass dependence of the pp spectrum close to the threshold can be reproduced by the S-wave pp final state interaction in the isospin I=1 state within the Watson-Migdal approach. However, because of our poor knowledge of the NN interaction near threshold and of the J/Ψ→γpp reaction mechanism and in view of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
119
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 134 publications
(131 citation statements)
references
References 46 publications
10
119
1
1
Order By: Relevance
“…For the latter case several explanations have been put forth, including scenarios that invoke NN bound states or so far unobserved meson resonances. However, it was also shown that a conventional but plausible interpretation of the data can be given simply in terms of the final-state interaction (FSI) between the produced proton and antiproton [16,17,18,19,20]. Specifically, calculations of our group, utilizing the Jülich NN model [21,22,23] and performed within the Watson-Migdal approach [24,25], could reproduce the mass dependence of thepp spectrum close to the threshold by the S -wavepp FSI for various decays [16,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…For the latter case several explanations have been put forth, including scenarios that invoke NN bound states or so far unobserved meson resonances. However, it was also shown that a conventional but plausible interpretation of the data can be given simply in terms of the final-state interaction (FSI) between the produced proton and antiproton [16,17,18,19,20]. Specifically, calculations of our group, utilizing the Jülich NN model [21,22,23] and performed within the Watson-Migdal approach [24,25], could reproduce the mass dependence of thepp spectrum close to the threshold by the S -wavepp FSI for various decays [16,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…[2]. Since the discovery of the X(1835) state, many models have been proposed to explain its properties [3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The DM2 experiment observed a "dip" in the cross section of the process e + e − → 3(π + π − ) near 1.9 GeV, confirmed later by the BaBar. The origin of the "dip" remains unclear, but the most popular explanation is based on a hypothesis of a presence of the under-threshold (pp) resonance discussed in many theoretical papers [15].…”
Section: Six Pion Productionmentioning
confidence: 99%